2021
DOI: 10.1007/s00292-021-00947-4
|View full text |Cite
|
Sign up to set email alerts
|

Wilhelm His Sr. and the development of paraffin embedding

Abstract: Paraffin histology is one of the most important and commonly-used laboratory techniques in diagnostic histopathology. The discovery of paraffin embedding is often attributed to the pathologist Edwin Klebs. Klebs was following the lead of Stricker, who embedded embryos in a mixture of hot stearin and white beeswax. We show that Klebs experimented with paraffin wax for embedding tumour tissue. But he quickly rejected it as unsuitable because paraffin wax did not infiltrate the tissue. One of Klebs’ correspondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…383-384;Hopwood, 1999Hopwood, , 2000Hopwood, , 2002Hopwood, , 2012; those techniques required an unbroken series of sections of consistent thickness. His addressed these problems by developing a protocol for the infiltration-embedding of embryos with paraffin wax (van der Lem et al, 2021). Edwin Klebs had introduced paraffin wax to histology (Klebs, 1867) but soon abandoned it (Klebs, 1869, pp.…”
Section: Wilhelm His's Early Researchmentioning
confidence: 99%
“…383-384;Hopwood, 1999Hopwood, , 2000Hopwood, , 2002Hopwood, , 2012; those techniques required an unbroken series of sections of consistent thickness. His addressed these problems by developing a protocol for the infiltration-embedding of embryos with paraffin wax (van der Lem et al, 2021). Edwin Klebs had introduced paraffin wax to histology (Klebs, 1867) but soon abandoned it (Klebs, 1869, pp.…”
Section: Wilhelm His's Early Researchmentioning
confidence: 99%
“…In his paper titled "The Etiology of Anthrax, Based on the Life History of Bacillus anthracis," Koch clarified the natural life cycle of Bacillus anthracis and effectively infected an- • Formalin, the current most popular fixative, was discovered in 1893 by Ferdinand Blum (1865-1969), who had placed an anthrax-infected mouse in formalin overnight and observed the hardening of its tissues [38]. Blum later demonstrated that formalin was effective at maintaining the colour and shape of tissues without affecting their microscopic structure [39] Tissue embedding [40] • Salomon Stricker (1834-1898) used a mixture of beeswax and stearin in 1864 to study frog embryos imals with the organism [44]. Koch's next major work in 1880 suggested that tuberculosis was also an infectious disease, a finding which was met with opposition by Rudolf Virchow, who viewed the disease to be a consequence of malfunctioning host cells without external causes.…”
Section: Dawn Of Microbiologymentioning
confidence: 99%
“…18 The change in the appearance of tissue indicates the effectiveness of the clearing process 19 before infiltration. Infiltration eliminates the clearing agent from the tissue 20 by diffusion to enhance impregnation with the most commonly used impregnating medium; molten paraffin wax. 2 The wax, which has diffused into the tissue after replacing the clearing agent, gets deposited in the tissues.…”
Section: Introductionmentioning
confidence: 99%